Computational analysis of the safe zone for the antegrade lag screw in posterior column fixation with the anterior approach in acetabular fracture: A cadaveric study. Issue 3 (March 2017) - Jung, Gu-Hee; Lee, Yongkoo; Kim, Joon-Woo; Kim, Ji-wan
Abstract: Objective: The fluoroscopically-guided procedure of antegrade posterior lag screw in posterior column fixation through anterior approach is technique-dependent and requires an experienced surgeon. The purpose of this study was to establish the safe zone for the antegrade posterior lag screw by using computational analysis. Method: The virtual three-dimensional model of 178 hemi-pelvises was created from the CT data (DICOM format) by using Mimics ® program, and were used to measure the safe zone of antegrade lag screw fixation on the inner table of the iliac wing, and the largest diameter of cylindrical implant inside safe zone. The central point (point A) of the cylinder was assessed and was compared with the intersection point (point B) between the linea terminalis and the anterior border of the sacroiliac articulation. Results: The safe zone was triangular with an average area of 670.4 mm 2 (range, 374.8–1084.5 mm 2 ). The largest diameter of the cylinder was a mean 7.4 mm (range, 5.0–10.0 mm). When height was under 156.3 cm, the diameter of the cylindrical implant was smaller than 7.0 mm (p < 0.001, regression coefficient = 0.09). The linear distance between points A and B was 32.5 mm (range, 19.2–49.3 mm). Point A was far enough away from the well-positioned anterior column plate to prevent collision between the two. Conclusion: The safe zone was shaped like a triangle, and was large enough for multiple screws. Considering the straight-line distance between points A and B, the central screw can be fixed without overlapping with the well-positioned anterior column plate at the point between holes 2 and 3.